Effects of Forward- and Emitted-Pressure Calibrations on the Variability of Otoacoustic Emission Measurements Across Repeated Probe Fits. Issue 6 (November 2019) - Maxim, Tom; Shera, Christopher A.; Charaziak, Karolina K.; Abdala, Carolina
Abstract : Objective: The stimuli used to evoke otoacoustic emissions (OAEs) are typically calibrated based on the total SPL measured at the probe microphone. However, due to the acoustics of the ear-canal space (i.e., standing-wave interference), this method can underestimate the stimulus pressure reaching the tympanic membrane at certain frequencies. To mitigate this effect, stimulus calibrations based on forward pressure level (FPL) can be applied. Furthermore, the influence of ear-canal acoustics on measured OAE levels can be compensated by expressing them in emitted pressure level (EPL). To date, studies have used artificial shallow versus deep probe fits to assess the effects of calibration method on changes in probe insertion. In an attempt to better simulate a clinical setting, the combined effects of FPL calibration of stimulus level and EPL compensation of OAE level on response variability during routine (noncontrived) probe fittings were examined. Design: The distortion component of the distortion-product OAE (DPOAE) and the stimulus-frequency OAE (SFOAE) were recorded at low and moderate stimulus levels in 20 normal-hearing young-adult subjects across a five-octave range. In each subject, three different calibration approaches were compared: (1) the conventional SPL-based stimulus calibration with OAE levels expressed in SPL; (2) FPL stimulus calibration with OAEs expressed in SPL; and (3) FPL stimulus calibration with OAEs expressed in EPL. Test and retest measurements were obtained during the same session and, in a subset of subjects, several months after the initial test. The effects of these different procedures on the inter- and intra-subject variability of OAE levels were assessed across frequency and level. Results: There were no significant differences in the inter-subject variability of OAE levels across the three calibration approaches. However, there was a significant effect on OAE intra-subject variability. The FPL/EPL approach resulted in the overall lowest test-rest differences in DPOAE level for frequencies above 4 kHz, where standing-wave interference is strongest. The benefit was modest, ranging on average from 0.5 to 2 dB and was strongest at the lower stimulus level. SFOAE level variability did not show significant differences among the three procedures, perhaps due to insufficient signal-to-noise ratio and nonoptimized stimulus levels. Correlations were found between the short-term replicability of DPOAEs and the benefit derived from the FPL/EPL procedure: the more variable the DPOAE, the stronger the benefit conferred by the advanced calibration methods. Conclusions: Stimulus and response calibration procedures designed to mitigate the effects of standing-wave interference on both the stimulus and the OAE enhance the repeatability of OAE measurements and reduce their dependence on probe position, even when probe shifts are small. Modest but significant improvements in short-term test-retest repeatability were observed in the mid- to high-frequency region when using combined FPL/EPL procedures. The authors posit that the benefit will be greater in a more heterogeneous group of subjects and when different testers participate in the fitting and refitting of subjects, which is a common practice in the audiology clinic. The impact of calibration approach on OAE inter-subject variability was not significant, possibly due to a homogeneous subject population and because factors other than probe position are at play.